La falta de aplicación del sistema procesal de la oralidad establecida en el código de procedimiento penal, en los procesos que se tramitan en el juzgado sexto de garantías penales tránsito en El Oro con sede en Piñas, año 2011. - Feijoo Quezada, Alicia Betzabeth (2012)
This paper presents an indispensable objective analysis of the oral system in Ecuador procedural law, using a comparison of historical evolution and its application in the present reality des term of considerable importance to the community. Orality should be considered as the current paradigm in criminal procedural law. This paradigm is born of a need to streamline, economize and above all meet the value of justice, where justice delayed becomes injustice. Given the importance of creating a culture not only the free exercise lawyer but also law students, the design of this study is a documentary research, analyzing legal and doctrinal sources. This theme will help to know everything related to the true procedural system of orality and its application in practice, to give a different approach that goes to the benefit of the accused, it is to orality processes faster and effective, but unfortunately they reduced to writing back to the past, thus leaving crime committed with impunity by the time involved or the delay that give these procedures.